Least Significant Bit (LSB) Modification Analysis With Alternate Insertion Message Technique On Image Media - Harahap, Ismail Sati Alom (Journal Basic Science and Technology, 2021)
One aspect of success in data communication is security. Data security can be done by using steganography. Steganography is a way to hide messages in the media in such a way that other people do not realize there is a message in the media. Many of the algorithms used in steganography one of which is the Least Significant Bit. In this research, the authors modify Least Significant Bit algorithms with Alternate Insertion method. Modification is doing of embedding and extracting messages process by changing the RGB values ??at each pixel of image data with confidential file by inserting message alternately and insertionly until the all message inserted. This steganography applications have input password that is used as the key of a message can't be opened in addition to the addressee so that the data will be kept confidential. The parameters used to measure the performance of the Least Significant Bit and Alternate Insertion are using runtime program and analysist algorithms of Big . The message insertion applications built by using C# (C Sharp) programming language. From the results of research that extracting process messages work faster than the embedding process. More larger of image in used it will be spend longer time to process the inserting message. Time complexity of algorithms (Big ) embedding and extracting processes obtained in testing the system is T (n) = (xy). From the results of research that extracting process messages work faster than the embedding process. More larger of image in used it will be spend longer time to process the inserting message. Time complexity of algorithms (Big ) embedding and extracting processes obtained in testing the system is T (n) = (xy). From the results of research that extracting process messages work faster than the embedding process. More larger of image in used it will be spend longer time to process the inserting message. Time complexity of algorithms (Big ) embedding and extracting processes obtained in testing the system is T (n) = (xy).